Competition Intensity, Uncertainty Environmental on the Use of Information Technology and Its Impact on Business Performance Small and Medium Enterprises (SMEs) - Purnama, Chamdan; Subroto, Waspodo Tjipto (International Review of Management and Marketing, 2016)
In the business world, the information technology revolution led to tremendous changes in competition, production, marketing and human resource management. The use of information technology is a vital component of business performance. By this study wanted to know iof competition intensity, uncertainty environment of business and the use of information technology and its impact on business performance. The sample number in this study are 130 respondences of small and medium enterprises (SMEs) printing management in East Java, using purposive sampling technique. Through testing with analysis of SEM (Structural Equation Modeling) the results of this study found that: First, competition intensity impact significant positive on the information technology investment. But competition intensity impact significant negative business performance small and medium enterprises (SMEs). Second, uncertainty environment of business impact significant positive on the business performance of small and medium enterprises (SMEs) and information technology investment. Third, information technology investment impact significant positive on the business performance of small and medium enterprises (SMEs). Keywords: Information technology, competition intensity, business performance, small and medium enterprises (SMEs). JEL Classification: L25